ANALYSIS OF PARENTAL AWARENESS OF TOILET TRAINING SUCCESS IN CHILDREN AGED 1-3 YEARS - Retno Palupi Yonni Siwi; Geystra Asmeranda Cahyaning Ciputri; Miftakhur Rohmah; Riza Tsalatsatul Mufida; Nining Istighosah (Journal for Quality in Women's Health, 2022)
The low success of toilet training in the community influenced the many mothers who do not train their children for chapters and bak in their place. The purpose of this study is the influence of parental awareness levels on the success of toilet training in children aged 1-3 years. The design of this study is observational with a cross sectional approach. The population using simple random sampling techniques obtained a sample of 33 respondents. The results showed that most of the respondents had a lesser level of awareness, which was 23 respondents. And most respondents have the ability to toilet training late, which is 23 respondents. There is an influence on the level of parental awareness on the success of toilet training. The level of parental awareness is able to increase the success of toilet training in children, parents want to motivate and train their children toilet training early on.